Grain size analysis and characterization of sedimentary environment of the surficial sediments of a sector of the Syrian coast (Al-Shqaifat - Latakia) - غدير, سامر (Latakia University Journal -Basic Sciences Series, 2022)
Detailed sedimentary study of a section of the Syrian coast (Al-Shqaifat - Latakia) was carried out in order to determine the grain size analysis and characterization of sedimentary environment. Twenty-six samples of surface sediments were collected along the coastal area during the autumn period of 2021. This research used an integrated methodology of analyzes and software to determine the nature of the sediments in the study area. The triangular diagrams showed the presence of five sedimentary models, namely Sand, Slightly Gravely Sand, Gravely Sand, Sandy Gravel, and finally Gravel. The results of grain size analyzes indicated that they are of coarse to very coarse grain size, poorly sorted, negatively skewed, and finally leptokurtic. These data confirm that the deposition occurred under high energy conditions with continuous mixing of sediments by waves and ocean currents, where erosion processes are active. The results of the linear discriminant function (LDF) analyzes performed on the samples indicated shallow coastal and marine sedimentation environments, and the results of the CM plot indicated that most of the samples were transported by rolling and to a lesser extent by graded suspension and rolling.